Analisis Gaya Kepemimpinan Kepala SMK Islam Gondanglegi Kabupaten Malang - Hafida, Nur; Wahyudi, Sigit; Aisam, Aisam (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out, analyze, and describe the leadership style of the principal of Smk Islam Gondanglegi and the factors that influence his leadership style. This study uses a qualitative research method of a case study approach for the relationship between the research variables and the hypothesis that must be proven. The result of this study is that the principal of SMK Islam Gondanglegi applies three leadership styles: participatory, instructional, and situational. This leadership style is used according to the situation, with the situational approach being used most often. Factors such as the ability of human resources and infrastructure facilities affect the effectiveness of leadership. Leadership development is carried out through awards, motivation, supervision, and intervention. This leadership has succeeded in improving staff motivation and school performance, both internally and externally